Meaningful interactions of alcoholic men in times of the COVID-19 pandemic - Souza, Samara Santos; Silva, Thainan Alves; Vieira, Larissa de Oliveira; Carvalho, Patrícia Anjos Lima de; Cruz, Diego Pires; Silva, Manuela de Jesus; Meira, Edméia Campos (O Mundo da Saúde, 2022)
This study aimed to understand the meaningful attitudes of alcoholic men and their expressions of feelings in the face of family and community interactions in times of the COVID-19 pandemic. This is a qualitative, descriptive, exploratory study, based on the Oral History of Life method. The participants of this study were five men who experience alcoholism, living in a municipality in the state of Bahia, accompanied by the Psychosocial Care Center for alcohol and other drugs. A semi-structured interview was used to collect information, from March to April 2021, through videoconferences through the Google Meet Digital Platform. The content of the oral reports was analyzed using a content analysis technique. It was observed that the significant attitudes of the alcoholic man were impacted by the unfolding of the pandemic, mainly due to the adoption of sanitary measures, such as social distancing. Some expressions of feelings were also identified of these men facing family and community interactions during the pandemic, such as fear, distrust, and affective insecurity, and social exclusion, in addition to expressions such as faith, gratitude, and hope. The participants’ discourses expressed attitudes of changes in social life and habits during this pandemic period, including the use of masks and gel alcohol in addition to the decrease in alcohol consumption for most of them. Therefore, the symbolic interactions arising from the pandemic scenario promoted protective attitudes that encompass self-care and collective care, in addition to interactions marked by family conflicts.